Ternary positive electrode material, preparation method thereof and battery

A multi-stage, temperature-controlled process addresses the cracking issue in ternary positive electrode materials, enhancing their mechanical strength and cycle performance by transforming the precursor into a rock salt phase, resulting in improved battery capacity and retention.

CN119181777APending Publication Date: 2024-12-24ZHEJIANG HUAYOU COBALT CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310745566.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

Ternary positive electrode materials used in lithium-ion batteries are prone to cracking during high-temperature calcination due to anisotropic grain growth, which adversely affects their cycle performance.

Method used

A method involving multiple reaction stages at progressively lower temperatures, starting with a first reaction at 235-300°C for 10-60 minutes, followed by mixing with a lithium source at 450-550°C for 2-5 hours, and finally sintering at 700-790°C for 12-18 hours, with grinding and sieving to produce a ternary positive electrode material.

Benefits of technology

The method enhances the mechanical strength of the ternary positive electrode material, reducing cracking and improving its cycle performance, with a first-cycle discharge capacity of 222.5-223.1 mAh/g and a 50-cycle capacity retention rate of 96.8-97.7%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181777A_ABST
    Figure CN119181777A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of battery materials, and provides a ternary positive electrode material, a preparation method thereof and a battery, and the preparation method comprises the following steps: placing a ternary precursor material at a first reaction temperature to react for a first reaction time to obtain a pretreatment product, and further uniformly mixing the pretreatment product with a compound containing a lithium source to obtain the ternary positive electrode material. And placing the mixture at a first reaction temperature for a second reaction time, placing the pre-sintered product obtained by the reaction at a second reaction temperature for a third reaction time to obtain a third product, grinding the third product, and screening to obtain the ternary positive electrode material, wherein the first reaction temperature is lower than the second reaction temperature, and the second reaction temperature is lower than the third reaction temperature; through the scheme, the problem that the material is easy to crack in the preparation process is avoided, and the cycle performance of the product is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and in particular, relates to a ternary positive electrode material, a preparation method thereof, and a battery. Background Art

[0002] The main components of lithium batteries include electrolyte, diaphragm, positive and negative electrode materials, etc. Among them, the positive electrode material is the key component of lithium batteries, and its capacity and stability directly determine the energy density and cycle life of the battery. At present, the positive electrode materials used in lithium-ion batteries on the market are usually lithium cobalt oxide, lithium iron phosphate and ternary positive electrode materials, but the theoretical capacity of lithium iron phosphate is low, the conductivity is small, the cycle performance is poor, and the lithium ion diffusion rate is slow and the rate performance is poor; lithium cobalt oxide is the earliest positive electrode material used, but it is expensive, has low specific capacity and poor safety; in contrast, the ternary positive electrode material contains three transition metals, Ni, Co and Mn. Under the synergistic effect of the three elements, it has high specific capacity and excellent low-temperature cycle performance advantages, which also makes the status of ternary positive electrode materials in the lithium battery industry steadily rise. Ternary positive electrode materials are prepared by mixing ternary precursor materials with lithium and then calcining them at high temperature. However, during the high-temperature calcination process, anisotropic grain growth will cause the particle surface to crack easily, seriously affecting its cycle performance. Summary of the invention

[0003] The purpose of the present application is to provide a method for preparing a ternary positive electrode material, a ternary positive electrode material and a battery, aiming to solve the problem of easy cracking of the ternary positive electrode material during the preparation process.

[0004] In order to achieve the above application purpose, the technical solution adopted in this application is as follows:

[0005] In a first aspect, the present application provides a method for preparing a ternary positive electrode material, comprising the following steps:

[0006] placing the ternary precursor material at a first reaction temperature and reacting for a first reaction time to obtain a pretreated product;

[0007] The pre-treated product is uniformly mixed with a compound containing a lithium source, and reacted at a second reaction temperature for a second reaction time to obtain a pre-sintered product;

[0008] Placing the pre-sintered product at a third reaction temperature and reacting for a third reaction time to obtain a third product, and grinding the third product and sieving to obtain a ternary positive electrode material;

[0009] Wherein, the first reaction temperature is lower than the second reaction temperature, and the second reaction temperature is lower than the third reaction temperature.

[0010] Preferably, the step of placing the ternary precursor material at a first reaction temperature and reacting for a first reaction time to obtain a pretreated product comprises:

[0011] The first reaction temperature is 235-300°C, the first reaction time is 10-60 minutes, and the ternary precursor material Ni 1-x-y Co x Mn y (OH)2 is placed in a reaction device, reacted at a first reaction temperature for a first reaction time, to obtain a pretreated product, wherein 0≤x+y≤0.2.

[0012] Preferably, the step of uniformly mixing the pretreated product with the compound containing a lithium source comprises:

[0013] The pretreatment product and the compound containing the lithium source are placed in a mill and mixed evenly, wherein the molar ratio of the pretreatment product to the compound containing the lithium source is Li:(Ni+Co+Mn)=1-1.1.

[0014] Preferably, the step of uniformly mixing the pretreated product with the compound containing a lithium source, and reacting at a second reaction temperature for a second reaction time to obtain a pre-sintered product comprises:

[0015] The second reaction temperature is 450-550° C., and the second reaction time is 2-5 hours. A uniform mixture of the pretreated product and the compound containing a lithium source is placed in a reaction device, and reacted at the second reaction temperature for a second reaction time to obtain a pre-sintered product.

[0016] Preferably, the step of placing the pre-sintered product at a third reaction temperature for a third reaction time to obtain a third product, and grinding the third product and then sieving to obtain a ternary positive electrode material comprises:

[0017] The third reaction temperature is 700-790°C, the third reaction time is 12-18h, the pre-sintered product is placed in a reaction device, reacted at the third reaction temperature for a third reaction time, to obtain a third product, the third product is ground and sieved to obtain a ternary positive electrode material LiNi 1-x-y Co x Mn y O2, where 0≤x+y≤0.2.

[0018] Preferably, the ternary precursor material Ni 1-x-y Co x Mn y The average particle size D50 of (OH)2 is 8-20 μm, and the specific surface area is 5-15 m 2 / g.

[0019] Preferably, the average particle size D50 of the compound containing a lithium source is 4 to 20 μm.

[0020] In a second aspect, the present application provides a ternary positive electrode material, which is prepared by the method described in any one of the first aspects above.

[0021] Preferably, the average particle size D50 of the ternary positive electrode material is 8 to 20 μm, and the specific surface area is 0.1 to 0.5 m 2 / g, the shape is spherical or quasi-spherical, and there is no crack on the surface of the material.

[0022] In a third aspect, the present application provides a battery, wherein the positive electrode sheet of the battery contains the ternary positive electrode material as described in the second aspect above, the first cycle discharge capacity of the battery is 222.5-223.1 mAh / g, and the 50-cycle capacity retention rate is 96.8-97.7%.

[0023] Beneficial effects of this application

[0024] The present application provides a method for preparing a ternary positive electrode material, comprising: placing a ternary precursor material at a first reaction temperature to react for a first reaction time to obtain a pretreated product, further mixing the pretreated product with a compound containing a lithium source, and placing the pretreated product at a second reaction temperature to react for a second reaction time, placing the pre-sintered product obtained by the reaction at a third reaction temperature to react for a third reaction time to obtain a third product, grinding the third product, and sieving to obtain a ternary positive electrode material; wherein the first reaction temperature is lower than the second reaction temperature, and the second reaction temperature is lower than the third reaction temperature; in the present application, placing the ternary precursor material at the first reaction temperature to react for the first reaction time can cause part of the internal structure of the ternary precursor material to be transformed from a layered phase to a rock salt phase, thereby improving the mechanical strength of the material, avoiding the problem of easy cracking in the preparation process, and improving the cycle performance of the product. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 It is a flow chart of a method for preparing a ternary positive electrode material provided in an embodiment of the present application;

[0027] Figure 2 is a thermogravimetric curve of the ternary precursor material provided in the embodiment of the present application;

[0028] Figure 3 is the X-ray diffraction pattern of the pre-treated product provided in the examples of the present application;

[0029] Figure 4 is an electron microscope image of the pre-treated product provided in the examples of the present application;

[0030] Figure 5 This is an electron microscope image of the ternary positive electrode material obtained in Example 1 of the present application;

[0031] Figure 6 This is an electron microscope image of the ternary positive electrode material obtained in Comparative Example 1 of the present application. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] For the convenience of description, the descriptions of "first", "second", etc. in the present invention are only set for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various implementation methods can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0034] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0036] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0037] In the prior art, ternary positive electrode materials are prepared by mixing ternary precursor materials with lithium and then calcining them at high temperature. However, during the high-temperature calcination process, anisotropic grain growth will cause the particle surface to crack easily, seriously affecting its cycle performance. In this regard, the present application proposes a method for preparing a ternary positive electrode material.

[0038] Figure 1 A flow chart of a method for preparing a ternary positive electrode material provided in an embodiment of the present application is shown.

[0039] Reference Figure 1 The present invention provides a method for preparing a ternary cathode material, comprising the following steps:

[0040] Step S100: placing the ternary precursor material at a first reaction temperature and reacting for a first reaction time to obtain a pretreated product;

[0041] Step S101: uniformly mixing the pre-treated product with a compound containing a lithium source, and reacting the mixture at a second reaction temperature for a second reaction time to obtain a pre-sintered product;

[0042] Step S102: placing the pre-sintered product at a third reaction temperature and reacting for a third reaction time to obtain a third product, grinding the third product, and then sieving to obtain a ternary positive electrode material;

[0043] Wherein, the first reaction temperature is lower than the second reaction temperature, and the second reaction temperature is lower than the third reaction temperature.

[0044] Among them, the ternary precursor material is a high nickel material, which can be Ni 1-x-y Co x Mn y (OH)2, where 0≤x+y≤0.2.

[0045] It should be noted that the ternary precursor material Ni 1-x-y Co x Mn y (OH)2 is a secondary particle formed by the agglomeration of primary particles in the form of a spherical, quasi-spherical or ellipsoidal sample, with an average particle size D50 of 8 to 20 μm and a specific surface area of ​​5 to 15 m 2 / g, and the diameter distance is 0.3~1.1.

[0046] The average particle size D50 of the compound containing a lithium source is 4 to 20 μm. The compound may be one or more of lithium hydroxide, lithium carbonate, lithium nitrate, or other lithium-containing compounds, which is not limited in the present application.

[0047] Among them, the equipment for setting the reaction temperature can be a tubular furnace, a sintering furnace, etc., that is, the preparation process of the ternary positive electrode material can be carried out in a tubular furnace or a sintering furnace.

[0048] It should be noted that the calculation formula for the diameter distance is as follows:

[0049] U=(D90-D10) / D50

[0050] Among them, U represents the diameter distance; D90 represents the particle size corresponding to when the cumulative particle size distribution number of the material reaches 90%; D50 represents the particle size corresponding to when the cumulative particle size distribution number of the material reaches 50%; D10 represents the particle size corresponding to when the cumulative particle size distribution number of the material reaches 10%.

[0051] For example, the ternary precursor material Ni 1-x-y Co x Mn y (OH)2 is placed in a tubular furnace, the temperature in the tubular furnace is set to rise to a first reaction temperature, the ternary precursor material reacts at the first reaction temperature for a first reaction time to obtain a pretreated product, the pretreated product is evenly mixed with lithium hydroxide, and the reaction is carried out at a second reaction temperature for a second reaction time to obtain a pre-sintered product, the pre-sintered product is placed at a third reaction temperature for a third reaction time to obtain a third product, the third product is ground, and sieved to obtain a ternary positive electrode material.

[0052] In this embodiment of the present application, the ternary precursor material Ni 1-x-y Co x Mn y (OH)2 is reacted at a first reaction temperature for a first reaction time, so that most of the layered hydroxide is dehydrated and converted into a rock salt phase NiO compound. The mechanical strength of the material is increased, making it less likely to crack and produce fragments in subsequent reactions, thereby improving the cyclic performance of the product.

[0053] In another possible embodiment of the present application, the first reaction temperature is set to 235-300° C. and the first reaction time is set to 10-60 min in step S100. 1-x-y Co x Mn y (OH)2 is placed in a reaction device, reacted at a first reaction temperature and for a first reaction time to obtain a pretreated product.

[0054] The reaction equipment may be a tubular furnace, a sintering furnace, or the like.

[0055] Among them, the first reaction temperature is 235-300℃, for example, it can be: 240℃, 245℃, 250℃, 255℃, 260℃, 265℃, 270℃, 275℃, 280℃, 285℃, 290℃, 295℃, 300℃.

[0056] Among them, the first reaction time is 10 to 60 minutes, for example, it can be: 10 minutes, 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes, and 60 minutes.

[0057] For example, the ternary precursor material Ni 1-x-y Co x Mn y (OH)2 was placed in a tube furnace and reacted at 300°C for 30 minutes to obtain a pretreated product.

[0058] Specifically, Ni with a D50 of 10.5 μm is selected 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the gas flow rate was set to 300 mL / min, the reaction temperature was 300°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0059] During the reaction, the gas introduced into the tubular furnace can be oxygen or air to assist the material reaction.

[0060] Figure 2 The thermogravimetric curve of the ternary precursor material provided in the embodiment of the present application is shown. Figure 2 It can be seen that Ni 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor loses the impure water on the surface at 235°C, and the precursor is basically dehydrated at 300°C. If the temperature is further raised to 550°C, the hydroxide precursor is completely dehydrated and transformed into a metal oxide. Combined with the X-ray diffraction spectrum, below 235°C, the precursor mainly loses a small amount of adsorbed water on the surface, which does not affect the crystal structure of the precursor. At 300°C, most of the layered hydroxide is dehydrated and transformed into a rock salt phase NiO compound, but at this time there is still a small amount of layered hydroxide in the material, which belongs to the coexistence of two phases. Continue to heat up to 550°C, and the layered hydroxide is completely transformed into a rock salt phase NiO compound.

[0061] Therefore, refer to Figure 2, will Ni 0.89 Co 0.04 Mn 0.07 The first reaction temperature of the (OH)2 hydroxide precursor is set between the first inflection point temperature of 235°C and the second inflection point temperature of 300°C. The reaction is carried out for 10 to 60 minutes under the above temperature conditions to remove free water and part of the hydroxide to obtain a pretreated product.

[0062] Figure 3 The X-ray diffraction pattern (XRD) of the pre-treated product provided in the embodiment of the present application is shown. Figure 4 The electron microscope image of the pre-treated product provided in the embodiment of the present application is shown; Figure 3 The XRD diffraction spectrum was compared with the PDF standard card of NiO (NiO-PDF#78-0423) and the PDF standard card of Ni(OH)2 (Ni(OH)2-PDF#73-1520). The comparison results showed that the hydroxide precursor after the reaction at the first reaction temperature lost some hydroxide and converted into NiO rock salt phase. In addition, there were still some diffraction signals of layered phase. The pretreatment product was a coexistence state of layered and rock salt phases, and there was no other impurity phase; refer to Figure 4 It can be seen that the pre-treated product particles are intact without fragments or cracks.

[0063] In another possible embodiment of the present application, the step of uniformly mixing the pretreatment product with the compound containing a lithium source in step S101 includes: placing the pretreatment product and the compound containing a lithium source in a grinding equipment and mixing them evenly to facilitate subsequent sufficient reaction, wherein the molar ratio of the pretreatment product to the compound containing a lithium source is Li:(Ni+Co+Mn)=1~1.1.

[0064] Among them, the grinding equipment can be a ball mill, a column mill, a rod mill, a tube mill, a vertical roller mill, a disc mill, etc.

[0065] Exemplarily, the pretreated product obtained in step S100 is mixed with lithium hydroxide at a molar ratio of Li:(Ni+Co+Mn)=1.02, and mixed evenly in a ball mill.

[0066] In other embodiments of the present application, in step S101, the second reaction temperature is set to 450-550° C., and the second reaction time is 2-5 hours. Correspondingly, a uniform mixture of the pretreated product and the compound containing a lithium source is placed in a reaction device, and reacted at the second reaction temperature for a second reaction time to obtain a pre-sintered product.

[0067] Among them, the second reaction temperature is 450-550℃, for example, it can be: 450℃, 455℃, 460℃, 465℃, 470℃, 475℃, 480℃, 485℃, 490℃, 495℃, 500℃, 505℃, 510℃, 515℃, 520℃, 525℃, 530℃, 535℃, 540℃, 545℃, 550℃.

[0068] The second reaction time is 2 to 5 hours, for example, 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, or 5 hours.

[0069] Exemplarily, a uniform mixture of the pretreated product and lithium hydroxide is placed in a tube furnace and reacted at 500° C. for 2 hours to obtain a pre-sintered product.

[0070] In some embodiments of the present application, the third reaction temperature is set to 700-790° C. in step S102, and the third reaction time is 12-18 hours. Correspondingly, the pre-sintered product is placed in a tubular furnace, reacted at the third reaction temperature for a third reaction time, and a third product is obtained. After the third product is ground, it is sieved to obtain a ternary positive electrode material LiNi 1-x-y Co x Mn y O2.

[0071] Among them, the third reaction temperature is 700-790℃, for example, it can be: 700℃, 705℃, 710℃, 715℃, 720℃, 725℃, 730℃, 735℃, 740℃, 745℃, 750℃, 755℃, 760℃, 765℃, 770℃, 775℃, 780℃, 785℃, 790℃.

[0072] Among them, the third reaction time is 12 to 18 hours, for example, it can be: 12h, 12.5h, 13h, 13.5h, 14h, 14.5h, 15h, 15.5h, 16h, 16.5h, 17h, 17.5h, 18h.

[0073] Exemplarily, the pre-sintered product is placed in a tube furnace and reacted at 750° C. for 16 h to obtain a third product, which is ground and sieved to obtain a ternary positive electrode material LiNi 1-x-y Co x Mn y O2.

[0074] It should be noted that the ternary cathode material LiNi 1-x-y Co x Mn yO2 is a secondary particle formed by the agglomeration of primary particles in the form of a spherical, quasi-spherical or ellipsoidal sample, with an average particle size D50 of 8 to 20 μm and a specific surface area of ​​0.1 to 0.5 m 2 / g, the shape is spherical or quasi-spherical, and there is no crack on the surface of the material.

[0075] In this embodiment of the present application, a uniform mixture of the pretreated product and lithium hydroxide is calcined at a certain temperature for a certain period of time so that the two can fully react to generate a ternary positive electrode material LiNi 1-x-y Co x Mn y O2, where 0≤x+y≤0.2.

[0076] The following describes the invention in conjunction with specific embodiments.

[0077] Example 1

[0078] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 300°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0079] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0080] Example 2

[0081] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 250°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0082] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0083] Example 3

[0084] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 270°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0085] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0086] Example 4

[0087] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 300°C, and the reaction time was 60 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0088] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0089] Comparative Example 1

[0090] Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor is mixed with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, and the mixture is evenly mixed in a ball mill. The uniform mixture is placed in a tubular furnace, and the oxygen flow rate is controlled to be 300 mL / min. The heating rate is 5°C / min, and the temperature is raised to 500°C. The reaction is continued for 2 hours, and then the temperature is continued to be raised to 750°C at a rate of 2°C / min. The reaction is performed for 16 hours. After naturally cooling to room temperature, the mixture is taken out, ground and sieved to obtain a ternary positive electrode material.

[0091] Comparative Example 2

[0092] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 235°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0093] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0094] Comparative Example 3

[0095] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 350°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0096] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0097] Comparative Example 4

[0098] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 450°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0099] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0100] Comparative Example 5

[0101] Step 1: Select Ni with D50 of 10.5μm 0.89 Co 0.04 Mn 0.07 The (OH)2 hydroxide precursor was placed in a tubular furnace, the oxygen flow rate was set to 300 mL / min, the reaction temperature was 550°C, and the reaction time was 30 min. After the reaction was completed and the product was naturally cooled, it was ground and sieved to obtain a pretreated product.

[0102] Step 2: Mix the pretreated product obtained in the first step with lithium hydroxide in a stoichiometric ratio of Li:(Ni+Co+Mn)=1.02, mix them evenly in a ball mill, place the uniform mixture in a tubular furnace, control the oxygen flow rate to 300mL / min, and the heating rate to 5℃ / min. Heat to 500℃ and react for 2h, then continue to heat to 750℃ at a rate of 2℃ / min, react for 16h, cool naturally to room temperature, take out, grind and sieve to obtain a ternary positive electrode material.

[0103] Figure 5The electron microscope image of the ternary positive electrode material obtained in Example 1 of the present application is shown. Figure 6 The electron microscope image of the ternary positive electrode material obtained in Comparative Example 1 of the present application is shown. Figure 5 and Figure 6 It can be seen that the ternary positive electrode material particles obtained in Example 1 are intact without fragments and cracks, while the ternary positive electrode material particles obtained in Comparative Example 1 have obvious cracks and even a small amount of fragments.

[0104] Therefore, Ni 0.89 Co 0.04 Mn 0.07 The first reaction temperature of the (OH)2 hydroxide precursor is set between the first inflection point temperature of 235°C and the second inflection point temperature of 300°C, and the reaction is carried out under the above temperature conditions for 10 to 60 minutes to remove free water and part of the hydroxide therein, so that the hydroxide precursor after the reaction loses part of the hydroxide and is converted into a NiO rock salt phase, thereby improving the mechanical strength of the product, making it less likely to crack and produce fragments in the subsequent mixed lithium sintering stage. The above scheme can significantly improve the phenomenon of easy cracking of the ternary positive electrode material during high-temperature calcination, thereby improving the cycle stability of the ternary positive electrode material.

[0105] In addition, pre-burning and dehydrating the precursor at low temperature can increase the metal content in the precursor and increase the amount of mixed lithium loading to improve the production capacity of the ternary positive electrode material.

[0106] The ternary positive electrode materials obtained by sintering the above-mentioned Examples 1 to 4 and Comparative Examples 1 to 5 were mixed with conductive carbon black (super P) and polyvinylidene fluoride (PVDF) at a mass ratio of 90:5:5, and an appropriate amount of N-methylpyrrolidone (NMP) was added to control the solid content of the slurry to 41%. The mixture was evenly mixed in a high-energy planetary mixer to obtain a slurry with a uniform viscosity. The slurry was coated on aluminum foil using an automatic coating machine. The electrode was first placed in a 60°C blast drying oven to remove the surface NMP solution, and then dried in a 100-degree vacuum drying oven overnight. The dried electrode was punched into a positive electrode with a diameter of 12 mm and a thickness of 90 μm using a slicer. Lithium metal was used as the negative electrode. The button batteries were assembled in a glove box with a water and oxygen content of less than 0.5 ppm. They were placed on a battery tester and subjected to charge and discharge cycle tests at 45°C and 0.5C rate.

[0107] The performance of each battery is shown in the following table (test error ±1mAh / g):

[0108]

[0109] Through the above series of experiments, the present application found that by pre-calcining the precursor and controlling the first reaction temperature between the first inflection point temperature of 235°C and the second inflection point temperature of 300°C of the thermogravimetric curve of the ternary precursor material, the calcined product coexists in layered and rock salt phases, has high mechanical strength, is not prone to cracking and fragmentation in the subsequent mixed lithium sintering stage, and can significantly improve the phenomenon of easy cracking of the positive electrode material during high-temperature calcination, thereby improving the cycle stability of the positive electrode material, and the first-cycle discharge capacity of the battery made of the positive electrode material can reach 222.5-223.1 mAh / g, and the 50-week cycle capacity retention rate can reach 96.8-97.7%. When the calcination temperature is further increased (first reaction temperature > 300°C), the proportion of rock salt phase NiO compounds in the calcined product increases. When the temperature is increased to the third inflection point temperature of the thermogravimetric curve, the precursor will be completely transformed into a rock salt phase NiO compound. However, rock salt phase NiO is not easy to undergo lithiation and lithium insertion reactions, resulting in a low first-cycle discharge capacity of the final ternary positive electrode material. As shown in Comparative Example 5, the first-cycle discharge capacity is as low as 210.5 mAh / g.

[0110] In another embodiment of the present application, a ternary positive electrode material is provided, and the preparation process thereof includes:

[0111] The ternary precursor material Ni 1-x-y Co x Mn y (OH)2 (0≤x+y≤0.2) is pre-calcined at a low temperature between the first inflection point temperature of 235°C and the second inflection point temperature of 300°C of the thermogravimetric curve of the precursor for 10 to 60 minutes to remove free water and part of the hydroxide, and converted into nickel-cobalt-manganese oxide. The hydroxide precursor is a secondary particle spherical, quasi-spherical or ellipsoidal sample formed by the agglomeration of primary particles; the average particle size D50 of the precursor particles is 8 to 20 μm, and the diameter distance is 0.3 to 1.1; the specific surface area of ​​the precursor is 5 to 15 m 2 / g; the nickel cobalt manganese oxide obtained above and lithium hydroxide monohydrate are uniformly mixed in a stoichiometric ratio of Li: (Ni + Co + Mn) = 1.02, and then sintered. During the sintering process, the oxygen flow rate is controlled to be 300 mL / min, pre-sintered at 450-550°C for 2-5h, and then heated to 700-790°C at a heating rate of 2°C / min for 12-18h, and naturally cooled to room temperature, wherein the average particle size D50 of the lithium hydroxide monohydrate particles is 4-20 μm; the product obtained by the above sintering is ground and sieved to obtain the ternary positive electrode material LiNi 1-x-y Co x Mn y O2.

[0112] In another embodiment of the present application, a battery is provided, wherein the positive electrode sheet of the battery comprises the ternary positive electrode material LiNi prepared in the above embodiment. 1-x-y Co x Mn y O2 (0≤x+y≤0.2), the first cycle discharge capacity of the battery is 222.5-223.1 mAh / g, and the 50-cycle capacity retention rate is 96.8-97.7%.

[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.

Claims

1. A method for preparing a ternary positive electrode material, characterized in that: The following steps are involved: placing the ternary precursor material at a first reaction temperature and reacting for a first reaction time to obtain a pretreated product; The pre-treated product is uniformly mixed with a compound containing a lithium source, and reacted at a second reaction temperature for a second reaction time to obtain a pre-sintered product; Placing the pre-sintered product at a third reaction temperature and reacting for a third reaction time to obtain a third product, and grinding the third product and sieving to obtain a ternary positive electrode material; Wherein, the first reaction temperature is lower than the second reaction temperature, and the second reaction temperature is lower than the third reaction temperature.

2. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The step of placing the ternary precursor material at a first reaction temperature and reacting for a first reaction time to obtain a pretreated product comprises: The first reaction temperature is 235-300°C, the first reaction time is 10-60 minutes, and the ternary precursor material Ni 1-x- y Co x Mn y (OH)2 is placed in a reaction device, reacted at a first reaction temperature for a first reaction time, to obtain a pretreated product, wherein 0≤x+y≤0.

2.

3. The method for preparing the ternary positive electrode material according to claim 1, characterized in that: The step of uniformly mixing the pretreated product with the compound containing a lithium source comprises: The pretreatment product and the compound containing the lithium source are placed in a mill and mixed evenly, wherein the molar ratio of the pretreatment product to the compound containing the lithium source is Li:(Ni+Co+Mn)=1-1.

1.

4. The method for preparing a ternary positive electrode material according to claim 1, characterized in that: The step of uniformly mixing the pre-treated product with the compound containing a lithium source, and reacting the mixture at a second reaction temperature for a second reaction time to obtain a pre-sintered product comprises: The second reaction temperature is 450-550° C., and the second reaction time is 2-5 hours. A uniform mixture of the pretreated product and the compound containing a lithium source is placed in a reaction device, and reacted at the second reaction temperature for a second reaction time to obtain a pre-sintered product.

5. The method for preparing the ternary cathode material according to claim 1, characterized in that: The step of placing the pre-sintered product at a third reaction temperature and reacting for a third reaction time to obtain a third product, and grinding the third product and sieving to obtain a ternary positive electrode material comprises: The third reaction temperature is 700-790°C, the third reaction time is 12-18h, the pre-sintered product is placed in a reaction device, reacted at the third reaction temperature for a third reaction time, to obtain a third product, the third product is ground and sieved to obtain a ternary positive electrode material LiNi 1-x-y Co x Mn y O2, where 0≤x+y≤0.

2.

6. The method for preparing the ternary cathode material according to claim 2, characterized in that: The ternary precursor material Ni 1-x-y Co x Mn y The average particle size D50 of (OH)2 is 8-20 μm, and the specific surface area is 5-15 m 2 / g.

7. The method for preparing a ternary cathode material according to claim 1, characterized in that: The average particle size D50 of the compound containing a lithium source is 4 to 20 μm.

8. A ternary positive electrode material, characterized in that: The ternary positive electrode material is prepared by the method according to any one of claims 1 to 7.

9. The ternary cathode material according to claim 8, characterized in that: The average particle size D50 of the ternary positive electrode material is 8 to 20 μm, and the specific surface area is 0.1 to 0.5 m 2 / g, the shape is spherical or quasi-spherical, and there is no crack on the surface of the material.

10. A battery, characterized in that: The positive electrode sheet of the battery contains the ternary positive electrode material as claimed in claim 8, the first cycle discharge capacity of the battery is 222.5-223.1 mAh / g, and the 50-cycle capacity retention rate is 96.8-97.7%.